Dissection of a murder : a novel - Murray, Jo (Dutton, 2026)
When Leila Reynolds is handed her first murder case, she's shocked by the victim: a well-known, well-respected judge, whose death sent shockwaves through the legal community. She's also incredulous--she's nowhere near experienced enough to handle such a high-profile assignment--but the defendant is insistent: he wants her, and only her, to represent him. Except he's refusing to talk. And if that wasn't complicated enough, Leila soon learns her opponent is the most ruthless prosecutor she's ever known: her husband. It's an impossible situation, yet Leila is determined to sway the jury--until she's blindsided once again by a shadowy figure from her past. Suddenly, Leila finds herself fighting not only for her client and marriage, but also to keep her own secrets buried. And if she has to rewrite the rules to win, so be it. --